2018
DOI: 10.1016/s2214-109x(18)30124-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoedema management to prevent acute dermatolymphangioadenitis in podoconiosis in northern Ethiopia (GoLBeT): a pragmatic randomised controlled trial

Abstract: Joint Global Health Trials scheme (from the Wellcome Trust, the UK Medical Research Council, and UK Aid).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 39 publications
3
78
0
2
Order By: Relevance
“…Whilst recall bias may have influenced the number of ADLAs reported, patients with mild/moderate and severe lymphoedema experienced an average of 6 and 10 respectively, which may be broadly extrapolated to 12 to 20 ADLAs per year. This aligns with the findings of a recent paper, which documented that podoconiosis patients with persistent lymphoedema experienced an average of 22 ADLA episodes a year [47]. Regardless of the lymphoedema severity, whilst experiencing an ADLA, patients' increased reliance on informal care, from their caregivers, to manage their symptoms and day-to-day activities was observed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Whilst recall bias may have influenced the number of ADLAs reported, patients with mild/moderate and severe lymphoedema experienced an average of 6 and 10 respectively, which may be broadly extrapolated to 12 to 20 ADLAs per year. This aligns with the findings of a recent paper, which documented that podoconiosis patients with persistent lymphoedema experienced an average of 22 ADLA episodes a year [47]. Regardless of the lymphoedema severity, whilst experiencing an ADLA, patients' increased reliance on informal care, from their caregivers, to manage their symptoms and day-to-day activities was observed.…”
Section: Discussionsupporting
confidence: 89%
“…Caring for patients during ADLAs was found to have a significant impact on caregivers, who needed to provide more support for symptom management and day-to-day tasks, including help with one-to-one tasks, such as limb washing. This is important as the WHO recommends regular limb hygiene to mitigate the morbidity associated with lymphoedema and enabling the continuity of such tasks during an ADLA, demonstrates caregivers' indispensable role as a human resource in providing the MMDP programmes' minimum package of care [10,12,47]. In addition, tasks outside the household, which often mitigated the household's economic loss, such as farming or tending the animals, were prominently provided by caregivers to assist patients' day-to-day activities during an ADLA.…”
Section: Discussionmentioning
confidence: 99%
“…The disease can be avoided by appropriate use of footwear and is treated through simple lymphoedema management measures, such as proper foot hygiene, bandaging, and exercises. 3 As such, detection of affected and at-risk populations is vital to ensure prevention and treatment measures are available for everyone in need.…”
mentioning
confidence: 99%
“…Simple hygiene-based interventions, typically involving daily washing of affected limbs with soap and water, are known to be effective for the management of lymphoedema in LF-endemic areas, resulting in a reduced incidence of ADLA [ 55 ]. Recent data have shown that a low-cost lymphoedema self-care package is effective in reducing the frequency and duration of ADLA in podoconiosis [ 56 ]. In this study, the package of care included instructions for foot hygiene, skin care, bandaging, exercises, and use of socks and shoes, and this was reinforced by trained members of the local community at regular monthly meetings.…”
Section: Morbidity Managementmentioning
confidence: 99%